2010
DOI: 10.1128/jvi.02635-09
|View full text |Cite
|
Sign up to set email alerts
|

The First Complete Papillomavirus Genome Characterized from a Marsupial Host: a Novel Isolate from Bettongia penicillata

Abstract: The first fully sequenced papillomavirus (PV) of marsupials, tentatively named Bettongia penicillata papillomavirus type 1 (BpPV1), was detected in papillomas from a woylie (Bettongia penicillata ogilbyi). The circular, double-stranded DNA genome contains 7,737 bp and encodes 7 open reading frames (ORFs), E6, E7, E1, E2, E4, L2, and L1, in typical PV conformation. BpPV1 is a close-to-root PV with L1 and L2 ORFs most similar to European hedgehog PV and bandicoot papillomatosis carcinomatosis virus types 1 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
14
0
1
Order By: Relevance
“…It helped to identify a core group of priority candidates and directly instructed the allocation of resources for further investigation. Research undertaken to identify potential pathogens relevant for the decline identified several pathogens (Smith et al 2008;Bennett et al 2010;Thompson et al 2010;Abdad 2011;Kaewmongkol et al 2011) and determined the antibody status towards selected viral infections (Pacioni et al 2014). Many of the disease investigations continue, and no definitive conclusion has been drawn on the ultimate cause of the decline.…”
Section: Discussionmentioning
confidence: 99%
“…It helped to identify a core group of priority candidates and directly instructed the allocation of resources for further investigation. Research undertaken to identify potential pathogens relevant for the decline identified several pathogens (Smith et al 2008;Bennett et al 2010;Thompson et al 2010;Abdad 2011;Kaewmongkol et al 2011) and determined the antibody status towards selected viral infections (Pacioni et al 2014). Many of the disease investigations continue, and no definitive conclusion has been drawn on the ultimate cause of the decline.…”
Section: Discussionmentioning
confidence: 99%
“…They are highly species specific and preferentially infect cutaneous or mucocutaneous epithelium. Papillomavirus genomes have been isolated and characterized from reptiles (Herbst et al, 2009), birds (Terai et al, 2002), marsupials (Bennett et al, 2010) and multiple other mammalian species (for recent review see Bernard et al (2010)) suggesting an evolutionary history spanning more than 300 million years (Herbst et al, 2009). Papillomaviruses replicate their genomes using the host enzymatic machinery, ensuring a high degree of proof reading with low mutation rates (Rector et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the size of the BPCV genome and the genes encoding the late proteins (L1 and L2) are most similar to those of the papillomaviruses. It has been theorized that the BPCVs are derived from an ancient coinfection recombination event between a polyomavirus and a papillomavirus (5).…”
mentioning
confidence: 99%